Proteomics studies to investigate alterations in the tau interactome under conditions of elevated cellular O‐GlcNAcylation: Molecular and cell biology/tau. (7th December 2020) - Choi, Jinkuk; Walther, Dirk M.; Bajrami, Bekim; Halftermeyer, Anais; Rajamohamed Sait, Hameetha Banu; Okugawa, Naomi; Engle, Sandra J.; Wei, Ru; Hering, Heike
Abstract: Background: Neurofibrillary tangles consist of tau protein aggregates and represent a hallmark pathology of Alzheimer's disease. Tau aggregation, specifically the formation of early aggregates, is believed to be neurotoxic. O‐linked glycosylation of proteins with β‐linked N‐acetylglucosamine (O‐GlcNAcylation) is exclusively mediated by two enzymes in cells, O‐GlcNAc transferase (OGT) and O‐GlcNAcase (OGA). Importantly, increasing O‐GlcNAcylation attenuates tau aggregation in cell‐free systems and cells and reduces tau pathology in various animal models, but the underlying molecular mechanism is still unclear. We aimed to determine how protein‐protein interactions of tau are affected by altered O‐GlcNAcylation levels in cells. Method: (1) Immunoprecipitation of tau complexes and nano LC‐MS/MS analysis (IP‐MS) were performed to detect changes in tau binding proteins in HEK293T cells, upon elevated O‐GlcNAcylation by OGT overexpression and OGA inhibition. (2) Proximity labeling by TurboID, an engineered biotin ligase, fused to either wild‐type or O‐GlcNAcylation‐resistant mutant tau and nano LC‐MS/MS analysis were performed to assess changes in the proximity of tau to other proteins in iPSC‐derived human cortical neurons (iN), after increasing O‐GlcNAcylation by OGA inhibition. Result: (1) We detected proteins that constitutively or differentially interact with tau from IP‐MS experiments in HEK293T cells. Microtubule and cytoskeletal proteins were consistently bound to tau regardless of changes in cellular O‐GlcNAcylation. RNA binding proteins and ribosomal proteins increased but cytosolic/exosome proteins and chaperone proteins decreased their interaction with tau upon elevated cellular O‐GlcNAcylation. (2) Proximity labeling of proteins by TurboID‐tau in iN successfully identified microtubule‐associated proteins and proteins that were previously reported to interact with tau in the brain. Interestingly, six proteins significantly changed their proximity to O‐GlcNAcylation‐resistant mutant tau, whereas increased O‐GlcNAcylation by OGA inhibition did not change the proximity labeling profile of wild‐type or mutant tau proteins. Conclusion: These results demonstrate that increasing cellular O‐GlcNAcylation does not significantly alter the general subcellular localization of tau, but affects its interaction with specific binding partners, some of which were previously implicated to play important a role in neurodegeneration. These data may provide novel mechanistic insights into how O‐GlcNAcylation impacts tau pathology.